Gene expression in bovine embryos derived from oocytes with different developmental competence collected at the defined follicular developmental stage - Němcová, Lucie; Machatková, Marie; Hanzalová, Kateřina; Horáková, Jindra; Kaňka, Jiří (Theriogenology, 2006)
The aim of this study was to compare the expression of selected genes in bovine embryos developed from oocytes with different developmental competence. Four oocyte populations were collected, separately either from small (2-5 mm) or medium (6-10 mm) follicles, in the growth/stagnation (G/S) or dominance/regression (D/R) stage of the first follicular wave. They were matured, fertilized and cultured to D7 or D8 blastocysts by a standard protocol. Poly (A)+ mRNA was extracted from pooled blastocysts and the expression of bax-alpha (Bax), connexin 43 (Cx 43) and connexin 31 (Cx 31) was estimated using real-time RT-PCR. The cleavage rates were significantly higher in oocytes collected from both medium and small follicles, (p < or = 0.05 and p < or = 0.01, respectively) in the G/S than in the D/R stage. There were no significant differences in the D7 blastocyst rates between oocytes from both medium and small follicles in the G/S or D/R stage. But the D8 blastocyst rate was significantly higher in oocytes from small follicles in the G/S stage compared with those in the D/R stage. The relative abundance of Bax and Cx 31 made no significant difference in both D7 and D8 blastocysts developed from oocytes collected from medium or small follicles in the G/S or D/R stages. But the relative abundance of the Cx 43 transcript was significantly higher in D8 blastocysts developed from oocytes collected from both medium and small follicles in the G/S stage compared with those in the D/R stage. We conclude that the relative abundance of Cx 43 can be used as a marker of developmental potential for embryos derived from oocytes with different developmental competence because the level of Cx 43 transcript was greater in embryos derived from oocytes with greater developmental competence compared with those derived from oocytes with lesser developmental competence.
Keywords: Cattle; financování organizované; Animals; skot; Female; Embryo, Mammalian; ženské pohlaví; blastocysta; Oocytes; ovariální folikul; oocyty; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; protein X asociovaný s bcl-2; Blastocyst; RNA, Messenger; Financing, Organized; Reverse Transcriptase Polymerase Chain Reaction; Connexin 43; Embryonic Development; Gene Expression; exprese genu; konexin 43; konexiny; zvířata; embryonální vývoj; Ovarian Follicle; bcl-2-Associated X Protein; embryo savčí; Connexins